Transcriptomic profiling with vascular tension analyses reveals molecular targets and phenotypes in preeclamptic placental vasculature - Zhang, Eryun; Zhou, Tao; Zheng, Qiutong; Zheng, Xiaomin; Zhang, Yingying; Liu, Bailin; Tang, Jiaqi; Xu, Zhice (Frontiers in Endocrinology, 2024)
Introduction The placental vascular system plays an important role in the development of pregnancy hypertension in preeclampsia. The gene profiles of whole placental tissue (containing blood vessels and many other structural components) and pure vascular tissue should be very different. All previous reports using RNA-seq analysis in the placenta have tested its whole tissue or the villous part, and thus the gene profiles in the pure placental blood vessels are unknown. Methods This study was the first to address this point with RNA-seq in human placenta at the transcript level. Isolated placental micro-vessels from normal and preeclamptic pregnancies were used for RNA-seq analysis, real-time quantitative polymerase chain reaction (RT-qPCR) verification, and vascular function tests. Furthermore, a vascular function-centric core network was constructed to show the gene-gene interactions and gene-function associations in the placental vessel system. Results Differential expression analysis identified a total of 486 significantly changed transcripts. Bioinformatics analysis further confirmed that multiple genes were highly related to blood vessel and placental phenotypes. Several hub genes, including ELMO1, YWHAE, and IL6ST, were significantly reduced in the placental vessels in preeclampsia. Vascular tension experiments showed that angiotensin II-mediated vasoconstriction and exogenous NO donor sodium nitroprusside-induced vasodilation were decreased, while phenylephrine-mediated vascular responses were unchanged in placental micro-vessels in preeclampsia. Discussion The results provide important insights into the pathological process in the placental vasculature in preeclampsia and offer great potential for further investigation of these molecular targets in the human placental vascular system.